PENGARUH PENYUSUNAN ANGGARAN PARTISIPATIF, MOTIVASI KERJA, KOMITMEN ORGANISASI TERHADAP KINERJA APARATUR PEMERINTAH DAERAH DENGAN DIMODERASI OLEH BUDAYA ORGANISASI (Studi Kasus pada Pemerintah Kota Yogyakarta) - Dirgahayu Maulina (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Abstract This study aims to determine the effect of participatory budget, work motivation, organizational commitment to the performance of local government officials to be moderated by the organization's culture. The population in this study is SKPD in the local government area in Yogyakarta. The sampling method with purposive sampling. Samples taken are employees who had working period of 1 year with a high school education and participate in the process of participatory budgeting with a sample of 71. The results of this study indicate that participatory budgeting has no significant effect on the performance of local government officials, motivation positive effect on the performance of the apparatus local government, organizational commitment positively affects the performance of local government officials, the organizational culture is not a positive influence on the relationship between participatory budget on the performance of local government officials, the organizational culture is not a positive influence on the relationship between motivation and performance of local government officials, the organizational culture had no effect positively to the relationship between organizational commitment and performance of local government officials.